Peningkatan Hasil Belajar Siswa Dalam Pembelajaran IPS Dengan Menggunakan Model Cooperative Learning Group Investigation di Sd N 09 Air Pacah Kota Padang - Hamimah , (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
This study was conducted based on observations made in class III SD N 09 Air Pacah, the city of Padang, that low student learning outcomes in learning Social Science (SS). This is due to learning is dominated by teachers, so that students were passive in learning. One effort that can be done to improve the learning process is to use the model of Cooperative Learning Group Investigation (CLGI). The purpose of this study was to describe improving student learning outcomes in social studies learning by using a model CLGI in class III SD N 09 Air Pacah Padang.his research was classroom action research (CAR), which was conducted in two cycles, each cycle consisting of four phases of research, namely planning, action, observation and reflection. To obtain research data, three instruments were used, namely sheets observations, field notes, and sheet tests, which were analyzed by using qualitative and quantitative data analysis. The subjects were students of class III SD N 09 Air Pacah Padang.The results showed that the model CLGI can improve student learning outcomes of third grade of public elementary school 09 Air Pacah, Padang. In the first cycle of student learning outcomes obtained the average value 67.05, with qualifications enough (C), and the second cycle increased into 77, with qualification good (B). Based on these results, it means 17 (70.83%) the student has been declared complete in learning social studies using models CLGI.